Pharmacological treatment for psychotic depression. - Wijkstra, J; Lijmer, J; Balk, F; Geddes, J; Nolen, W (2005)
BACKGROUND: Regarding the pharmacological treatment of psychotic depression there is uncertainty about the effectiveness of an antidepressant alone compared to the combination of an antidepressant and an antipsychotic. OBJECTIVES: To compare the clinical effectiveness of pharmacological treatments for patients with a psychotic depression: antidepressant monotherapy, antipsychotic monotherapy, and the combination of an antidepressant and an antipsychotic, compared with each other and/or with placebo. SEARCH STRATEGY: (1) The Cochrane Central Register of Controlled Trials (CENTRAL) was screened with the terms depressive disorder and drug treatment (April 2004). (2) MEDLINE (1966 to April 2004) and EMBASE (1980 to April 2004) were searched using terms with regard to treatment of unipolar psychotic depression.(3) Reference lists of related reviews and reference lists of all identified studies were searched.(4) Personal communications. SELECTION CRITERIA: All randomised controlled trials (RCTs) with patients with major depression with psychotic features as well as RCTs with patients with major depression with or without psychotic features which reported on the subgroup of patients with psychotic features separately. DATA COLLECTION AND ANALYSIS: Two reviewers assessed the methodological quality of the included studies, according to the Cochrane Handbook criteria. Data were entered into RevMan 4.2.5. We used intention-to-treat data. For dichotomous efficacy outcomes, the relative risk with 95% confidence intervals (CI) was calculated. For continuously distributed outcomes, it was not possible to extract data from the RCTs. Regarding the primary harm outcome, only overall drop-out rates were available for all studies. MAIN RESULTS: The search identified 3333 abstracts, but only 10 RCTs with a total of 548 patients could be included in the review. Due to clinical heterogeneity, few meta-analyses were possible. We found no conclusive evidence that the combination of an antidepressant and an antipsychotic is more effective than an antidepressant alone (two RCTs; RR 1.44, 95% CI 0.86 to 2.41), but a combination is more effective than an antipsychotic alone (three RCTs; RR 1.92, 95% CI 1.32 to 2.80). There were no statistically significant differences in the overall drop-out rates between any of the treatments, neither in individual studies nor after pooling of studies. AUTHORS' CONCLUSIONS: Treatment with an antipsychotic alone is not a good option. Starting with an antidepressant alone and adding an antipsychotic if the patient does not respond or starting with the combination of an antidepressant and an antipsychotic both appear appropriate options for patients with psychotic depression. In clinical practice the balance between risks and benefits suggests that initial antidepressive monotherapy and adding an antipsychotic if there is inadequate response should be the preferred treatment strategy for many patients. The general lack of available data limits confidence in the conclusions drawn.